Some Upper Matrix Bounds for the Solution of the Continuous Algebraic Riccati Matrix Equation - Zübeyde Ulukök; Ramazan Türkmen (Journal of Applied Mathematics)
We propose diverse upper bounds for the solution matrix of the continuous algebraic Riccati matrix equation (CARE) by building the equivalent form of the CARE and using some matrix inequalities and linear algebraic techniques. Finally, numerical example is given to demonstrate the effectiveness of the obtained results in this work as compared with some existing results in the literature. These new bounds are less restrictive and provide more efficient results in some cases.